Endoscopic Findings and Histopathological Pattern in Patients with Chronic Dyspepsia at Panti Rapih Hospital Jogjakarta - Haryanto Rahardjo; Siti Nurdjanah; Putut Bayupurnama (The Indonesian Society for Digestive Endoscopy, 2008)
Background: To determine the relationship between clinical manifestation of chronic dyspepsia and endoscopic findings along with histopathological pattern by descriptive analysis. Methods: This study was a retrospective study. Subjects were patients with chronic dyspepsia who underwent endoscopic examination and gastric biopsy between June 2005 and July 2006. Result: There are 10.17% normal endoscopic results of 79 patients with chronic dyspepsia and almost 90% show abnormal result in endoscopic examination. The histopathological pattern is normal in 2.53% and 97.47% demonstrate abnormal result. The prevalence of Helicobacter pylori due to gastric ulcer is 1.26% and chronic atrophic gastritis is 3.80%. Conclusion: Most of chronic dyspepsia patients have abnormal endoscopic and histopathologic result. Keywords: chronic dyspepsia, endoscopic findings, histopathological pattern, Helicobacter pylori